The senior year students' persistence profile of UMTAS (University of Muhammadiyah Tasikmalaya) - Luanda, Aditia; Isti'adah, Feida Noor Laila; Nugraha, Agung (ProGCouns: Journal of Professionals in Guidance and Counseling, 2020)
This study aims to determine the profile of senior year students at the end of class 2015 that have been studied for 4 years or undergraduate students (S1). This descriptive study was conducted to 10 study programs (S1) at the University of Muhammadiyah Tasikmalaya with a sample number of 142 students. Measuring instrument employed in the form of a questionnaire multiple choice that refers to the grand theory of Pury (Lopez, 2009), which was designed by the researcher in 2019. The results revealed that the persistence of 2015 students was in high category with a percentage of 77.33%. The number of final-level students in the high category of 85% or 121 students, in addition there were 14% or 20 students who belonged to the medium category and 1% or 1 student was in the low category. This indicates that in general, the senior students at the Universitas Muhammadiyah Tasikmalaya have demonstrated maximum persistence in each dimension, including having high desire and awareness to pursue their goals, doing hard effort sustainably, instilling persistent character in resolving the problems, as well as the students can survive and move forward despite the challenges and difficulties in achieving their objectives.